Sound, Music, War and Violence: Listening from the Archive - Annegret Fauser (Transposition, 2020)
When the sonic remnants of violence and war survive in archives as being inscribed in such media as paper, it can be a challenge to engage with their aurality, all the more because subsequent audiovisual representations might overlay such embodied past experiences with different musical signifiers. Drawing on examples from the two world wars of the twentieth century, this contribution discusses which positionalities an author might embrace when listening to war and violence through the presence of music, sound, and silence in the archives.